2022
DOI: 10.3390/ma15124093
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Meso-Scale and Time-Efficient Sub-Track-Scale Thermomechanical Model for Directed Energy Deposition

Abstract: Thermally-induced distortion and residual stresses in parts fabricated by the additive manufacturing (AM) process can lead to part rejection and failure. Still, the understanding of thermo–mechanical behavior induced due to the process physics in AM process is a complex task that depends upon process and material parameters. In this work, a 3D thermo-elasto-plastic model is proposed to predict the thermo–mechanical behavior (thermal and distortion field) in the laser-directed energy deposition (LDED) process u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Yadollahi et al [9] found that longer inter-layer time intervals result in higher local cooling rates, thus leading to finer microstructures, higher tensile strength, and lower elongation-to-failure in DED-L 316 stainless steel samples. Other studies also show that the microstructural evolution of a metal DED-L part can be altered significantly by changing inter-layer time intervals [10][11][12][13]. A common observation is that the time dedicated to the dissipation of accumulated heat has a direct impact on microstructure and its phases.…”
Section: Introductionmentioning
confidence: 99%
“…Yadollahi et al [9] found that longer inter-layer time intervals result in higher local cooling rates, thus leading to finer microstructures, higher tensile strength, and lower elongation-to-failure in DED-L 316 stainless steel samples. Other studies also show that the microstructural evolution of a metal DED-L part can be altered significantly by changing inter-layer time intervals [10][11][12][13]. A common observation is that the time dedicated to the dissipation of accumulated heat has a direct impact on microstructure and its phases.…”
Section: Introductionmentioning
confidence: 99%